The Off-Label Use of Antineoplastics in Oncology Is Limited But Has Notable Scientific Support in a University Hospital Setting - Herrero Fernandez, Marta; Molina Villaverde, Raquel; Arroyo Yustos, Monica; Navarro Expósito, Fatima; Lopez Gonzalez, Jose Luis; Luque Infantes, Maria Rosario; Alvarez-Mon Soto, Melchor (Frontiers in Pharmacology, 2019)
Purpose: The off-label (OL) use of antineoplastic drugs for the treatment of various types of tumors in patients of different disease stages is becoming a common occurrence. The objective of this study was to analyze these patterns by quantification and characterization of the OL use of antineoplastic drugs and their level of scientific evidence in a medium/high-complexity Spanish general university hospital. Method: All oncology patients who underwent OL treatment with one or several antineoplastics during the 10 years from 2002 to 2012 were retrospectively selected. The use of these drugs was considered OL if they were used for indications, stages, lines of treatment, or chemotherapy schemes not reflected in the summary of product characteristics published by the European Medicines Agency at the time of prescription. To calculate the prevalence of patients who received one or more OL treatments during the study period, all patients whose primary or secondary diagnosis had been coded with the diagnoses included in the study were selected through the minimum basic data set (MBDS). This database was cross-referenced with that of the Farmatools® program (Dominion®), which collects information on all patients receiving chemotherapy to obtain the total number of patients who received chemotherapy in the hospital during this period. Results: In total, 684 patients and 866 OL treatments were included. The prevalence of patients undergoing OL treatment with antineoplastics was 6%. OL treatments were used mainly for breast, gynecological, lung, and gastric tumors. The most often-used antineoplastic was paclitaxel, followed by gemcitabine, carboplatin, vinorelbine, and capecitabine, which were used mainly in monotherapy and with palliative intent. A total of 56.1% of the OL schemes used had a level of evidence of 2A according to the National Comprehensive Cancer Network, and 55.3% had a level of evidence of 2B according to Micromedex®. Conclusion: The OL use of antineoplastics in oncology patients is limited; their use is mainly focused in a small group of tumors and at advanced stages of disease. OL use of antineoplastics occurs under palliative therapeutic strategies with a limited number of drugs, preferably off-patent drugs. In addition, these OL treatments have high levels of clinical evidence.